Pengaruh Model Pembelajaran Kooperatif Tipe Think Talk Write (TTW) Terhadap Hasil Belajar IPAS Kelas V SD Negeri 064973 Bhayangkara T.A 2024/2025 - Rosvelly Retno Sri Amanda Hutasoit; Nurmayani Nurmayani (Jurnal Ilmiah Dikdaya, 2026)
The purpose of this study was to determine the effect of the cooperative learning model type think talk write (TTW) on the learning outcomes of Class V Science Elementary School 064973 Bhayangkara Academic Year 2024/2025. This type of research is quasi-experimental. This study uses a pretest-posttest control group design, which means they (both groups) will be given a pretest and posttest. The data collection techniques used by the author are tests, interviews, observations and documentation. The sample in this study were 44 students in class VA and VB of SD Negeri 064973 Bhayangkara Academic Year 2024/2025. The data collection technique used was the t-test statistical test (t-test) using SPPS 26. Based on the results of the t-test, it is known that the value in the sig. (2-tailed) column is 0.000. Referring to the results obtained, when compared with the significance value of 0.05, it can be seen that 0.000 <0.05, and get tcount = 4.938 while ttable = 2.021 (tcount > ttable). This means that H0 is rejected and Ha is accepted, which means that there is a significant influence on the cooperative learning model of the think talk write (TTW) type on the learning outcomes of science in grade V students of SD Negeri 064973 Bhayangkara.